MobileVJ: A mobile app for a novel wearable human sensing system - Pavel Alexeenko (2016)
Over the years, technologies are in constantly progress, therefore its influence on human life cannot be unnoticed. The new technologies are now part of the daily life. They make life easier for everybody and they also provide improvements in all aspects of life. Nowadays, in health area exist numerous vital sensors as much as environmental and motion ones. Most of the time all sensors save their monitored data on a physical disk or through a mobile device. As you can imagine, thesedevicesgeneratehugedataandgroupthembecomesdifficult. Thesolutionforthis problem would be creating a mobile system which would be able to group the data at the time of collection and an API RESTfull which can maintain a safe and reliable communication with the module. Todeveloptheaggregatormodule,itwaschosentheAndroidplatform,whichwillbeusedthe Bluetooth technology to select the specific sensors that belong to external monitoring devices and also to the smartphone. It will be able to send the data instantly to a server with API RESTfull or store the data until a certain limit memory. To test the module operation, it will be used monitoring technologies such as VitalJacket, Zephyr HxM BI, VHB hemlet with environmental and motion sensors. This project would have a huge impact in the monetization of the athlete's health, both professional and amateurs, in remote monitoring of users in hospitals or even in risky lines of work such as firemen or policemen to be able to react on the spot if one of the employees find himself danger.